Recovery of High Purity Lignin and Digestible Cellulose from Oil Palm Empty Fruit Bunch Using Low Acid-Catalyzed Organosolv Pretreatment - Kinanthi Mondylaksita; Jorge A. Ferreira; Ria Millati; Wiratni Budhijanto; Claes Niklasson; Mohammad J. Taherzadeh (Agronomy, 2020)
The lignocellulosic residue from the palm oil industry, oil palm empty fruit bunch (OPEFB), represents a challenge to both producing industries and environment due to its disposal difficulties. Alternatively, OPEFB can be used for the production of valuable products if pretreatment methods, which overcome OPEFB recalcitrance and allow tailored valorization of all its carbohydrates and lignin, are developed. Specifically, high-value applications for lignin, to increase its contribution to the feasibility of lignocellulosic biorefineries, demand high-purity fractions. In this study, acid-catalyzed organosolv using ethanol as a solvent was used for the recovery of high-purity lignin and digestible cellulose. Factors including catalyst type and its concentration, temperature, retention time, and solid-to-liquid (S/L) ratio were found to influence lignin purity and recovery. At the best conditions (0.07% H2SO4, 210 °C, 90 min, and S/L ratio of 1:10), a lignin purity and recovery of 70.6 ± 4.9% and 64.94 ± 1.09%, respectively, were obtained in addition to the glucan-rich fraction. The glucan-rich fraction showed 94.06 ± 4.71% digestibility within 18 h at an enzyme loading of 30 filter paper units (FPU) /g glucan. Therefore, ethanol organosolv can be used for fractionating OPEFB into three high-quality fractions (glucan, lignin, and hemicellulosic compounds) for further tailored biorefining using low acid concentrations. Especially, the use of ethanol opens the possibility for integration of 1st and 2nd generation ethanol benefiting from the separation of high-purity lignin.